The lost opportunity from insufficient pollinators for global food supplies and human health - Smith, Matthew R.; Mueller, Nathaniel D.; Springmann, Marco; Sulser, Timothy B.; Garibaldi, Lucas A.; Gerber, James S.; Wiebe, Keith D.; Myers, Samuel S. (Elsevier, 2022)
Animal pollination supports agricultural production for many healthy foods, such as fruits, vegetables, nuts, and legumes, which provide key nutrients and protect against non-communicable diseases. Today, most crops receive suboptimal pollination because of reduced abundance and diversity of pollinating insects. We modelled the effects on current global human health from insufficient pollination by quantifying the pollinator-related crop yield gap and lost consumption of pollination-dependent foods by country and region, after accounting for global trade, economic behaviours, and food waste. We also estimated the lost economic value of crop production for the following three diverse case-study countries: Honduras, Nepal, and Nigeria.